Efektivitas Antibiotik Tetrasiklin Terhadap Bakteri Propionibacterium Acnes Dengan Metode Difusi Pada Pasien Acne Vulgaris pada Tahun 2022 - Alvin Andrian Susanto; Eka Silvia; Ade Utia; Muhamad Syafei Hamzah (CV. Jasa Sukses Abadi, 2022)
Acne vulgaris is a disorder of the pilosebaceous unit that appears mainly in adolescence. Most cases of acne present with polymorphic lesions, which consist of comedones, papules, pustules, and nodules of varying severity. Acne can cause a decrease in self-confidence because it can cause hypertrophic scars that can cause lifelong scars. Oral clindamicin has been used for a long time, but has a high risk of pseudomembranous colitis. Currently, clindamici is rarely used for the treatment of acne vulgaris, but it is still commonly used topically in combination with benzoyl peroxide.